THE EFFECT OF INVESTMENT OPPORTUNITY SET, LAGGED DIVIDEND AND MANAGERIAL OWNERSHIP ON DIVIDEND POLICY - Rossiana Sita Ayu Gennusi; Novera Kristianti Maharani (GoAcademica Research dan Publishing, 2021)
The purpose of this study is to examine the factors that influence dividend policy in companies in the consumption industry sector between 2017 and 2019. The market to book value of equity can be used to calculate the investment opportunity set, the lagged dividend can be calculated using the dividend payout ratio from the previous year, managerial ownership can be calculated as a percentage of total share ownership divided by total company shares, and dividend policy can be calculated using the dividend payout ratio. Purposive sampling procedures were used to collect data, and the results were analyzed using multiple linear regression analysis. This study drew 60 samples from a total population of 168. The data is secondary in nature and derived from financial statements. The results of hypothesis testing indicate that investment opportunity set, lagged dividend, and managerial ownership all have an effect on dividend policy. And, to a lesser extent, the investment opportunity set affects dividend policy, while lagged dividends have no effect on dividend policy.